Method of automated construction of explanatory dictionary of subject area - Кунгурцев, Алексей Борисович; Поточняк, Яна Владимировна; Силяев, Дмитрий Александрович (Technology audit and production reserves, 2015)
The article deals with the method of the automated construction of explanatory dictionary based on the processing of many texts from a specific subject area. The technology of selection and grouping of source texts, based on inter-document and intra-document clustering, which allows save significant terms in the dictionary. It is developed the procedure of selection of terms (individual words and phrases) from documents, based on the calculation of the frequency of their occurrence in the text. The technique of finding of synonyms, definitions, and using other dictionaries is proposed. The formula that allows you to estimate the time spent on the various stages of compiling the dictionary is given. The results of experiments that confirm the effectiveness of the proposed method of construction of dictionary of subject area are given. The proposed method of automatic compilation of the dictionary of subject area can be used to determine the stage of requirements for software products in information systems and artificial intelligence systems.